2017
DOI: 10.1093/gbe/evw305
|View full text |Cite
|
Sign up to set email alerts
|

LXRα and LXRβ nuclear receptors evolved in the common ancestor of gnathostomes

Abstract: Nuclear receptors (NRs) regulate numerous aspects of the endocrine system. They mediate endogenous and exogenous cues, ensuring a homeostatic control of development and metabolism. Gene duplication, loss and mutation have shaped the repertoire and function of NRs in metazoans. Here, we examine the evolution of a pivotal orchestrator of cholesterol metabolism in vertebrates, the liver X receptors (LXRs). Previous studies suggested that LXRα and LXRβ genes emerged in the mammalian ancestor. However, we show thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 34 publications
1
18
0
Order By: Relevance
“…Because previous studies used cell lines with uneven levels of LXRs or antibodies that do not discriminate between LXR␣ and LXR␤, we believe that our data sets represent the most accurate LXR binding repertoire described for macrophages (4,26,27). Recently, it was reported that LXR genes arose through a gene duplication event (50). However, it is unclear whether LXR␣ has acquired specialized functions related to lipid metabolism and immunity, losing its ability to regulate other genes, or whether an expansion of LXR␤-associated functions has occurred, resulting in LXR␣ occupying a reduced number of genomic sites in comparison.…”
Section: Discussionmentioning
confidence: 99%
“…Because previous studies used cell lines with uneven levels of LXRs or antibodies that do not discriminate between LXR␣ and LXR␤, we believe that our data sets represent the most accurate LXR binding repertoire described for macrophages (4,26,27). Recently, it was reported that LXR genes arose through a gene duplication event (50). However, it is unclear whether LXR␣ has acquired specialized functions related to lipid metabolism and immunity, losing its ability to regulate other genes, or whether an expansion of LXR␤-associated functions has occurred, resulting in LXR␣ occupying a reduced number of genomic sites in comparison.…”
Section: Discussionmentioning
confidence: 99%
“…Amphioxus possesses 10 paralogues of the FXR/LXR (Farnesoid X Receptor/Liver X Receptor) subfamily due to a lineage-specific duplication event (Lecroisey et al, 2012, Schubert et al, 2008, with one of them being a clear orthologue of vertebrate LXR. Phylogenetic approaches only clarified the orthology of 5 of the other receptors with vertebrate FXRs (Fonseca et al, 2017). Ligand binding has been characterized using transient transactivation assays for the amphioxus LXR with four different ligands (the synthetic molecule T0901317, and the natural ligands 24(S)-hydroxycholesterol, 25-hydroxycholesterol and 24(S),25epoxycholesterol).…”
Section: Cell-cell Communication Pathways In Amphioxus 707mentioning
confidence: 99%
“…Ligand binding has been characterized using transient transactivation assays for the amphioxus LXR with four different ligands (the synthetic molecule T0901317, and the natural ligands 24(S)-hydroxycholesterol, 25-hydroxycholesterol and 24(S),25epoxycholesterol). While the amphioxus LXR is able to bind and transactivate a reporter gene in the presence of these ligands, it shows a low binding affinity for them compared with its vertebrate orthologues (Fonseca et al, 2017).…”
Section: Cell-cell Communication Pathways In Amphioxus 707mentioning
confidence: 99%
“…The Lxrβ locus was lost in the fish phylum (Fonseca et al, 2017). Furthermore, zebrafish Lxrα binds and is activated by endogenous and synthetic ligands in a manner similar to human LXRα (Archer et al, 2008; Reschly et al, 2008).…”
Section: Introductionmentioning
confidence: 99%